Total Alkaloid and Saponin Content of the Ethanolic Leaf Extracts of Cassia alata, Chrysophyllum cainito, Cymbopogon citratus, Lantana camara, and Terminalia catappa - Ang, Aileen May Gabule; Manuales, Alkhen Dave Fuentes (Asian Journal of Biological and Life Sciences)
Introduction: Alkaloids and saponins are among the phytochemicals with promising medicinal value. Ethnopharmacological studies have shown that Cassia alata, Chrysophyllum cainito, Cymbopogon citratus, Lantana camara, and Terminalia catappa are traditional herbal plants worth investigating. Objectives: The need to generate knowledge about the phytochemistry of these plants, specifically the total alkaloid and saponin content, can be of vital significance for future-related researches and product development. Materials and Methods: The determination of total alkaloid and saponin content in the ethanolic leaf extracts of Cassia alata, Chrysophyllum cainito, Cymbopogon citratus, Lantana camara, and Terminalia catappa were determined spectrophotometrically and gravimetrically, respectively. Results and Discussion: The results reveal the presence of alkaloids in the ethanolic leaf extracts. Significant differences is observed in the order of 71.23 (L. camara) > 47.16 (C. alata) > 36.42 (C. citratus) > 6.99 (C. caimito) ~ 5.31 mg Atropine Equivalents/g sample (T. catappa). For the total saponin content, the ethanolic leaf extracts of C. cainito, L. camara, and T. catappa are statistically comparable but significantly higher than that of C. citratus and C. alata. Conclusion: The total alkaloid and saponin content in the ethanolic leaf extracts of C. alata, C. cainito, C. citratus, L. camara, and T. catappa vary depending on their taxonomic classification. Furthermore, the detection of alkaloids and saponins in the leaf ethanolic extracts provide scientific basis to support their medicinal value as potential sources of bioactive compounds.
Keywords: Ethanolic extracts; Saponin content.; Taxonomy-dependent; Total alkaloids